Penetapan Izin Poligami melalui Pengadilan Agama dalam Perspektif Hukum Positif di Indonesia - Azhari, Wildan Habib; Harahap, Yadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Basically everyone wants to get married only once in their life, but there are several reasons why people commit polygamy or get married two or three or four times. The causal factors referred to are internal factors from the family which resulted in the husband choosing to remarry, as regulated in positive law in Indonesia, that polygamy must go through a procedural procedure in a religious court and must fulfill certain reasons and conditions so that the religious court judge can grant the proposed polygamy permit.. This research is qualitative research with a normative juridical type of research, using a library research approach. The results of this research show that the case examination process in this research has been carried out in accordance with the provisions, and in legal fact the wife gave written permission to the husband to carry out polygamy so that the judge gave permission to the husband to carry out polygamy with his second wife.